The Impact of Research Methodology and Statistics Mastery on the Quality of Student Theses in Elementary School Teacher Education Department - Muhammad Yasin (STAI Hubbulwathan Duri, 2023)
Thesis is one of the biggest challenges for students. This is because students often do not understand the method of writing a thesis as a scientific paper. This research was carried out to examine the mastery of research methodology and statistics on the quality of student thesis. The research method used in this study is quantitative research. The results of this study then found a positive and very significant relationship between mastery of educational research methodology material and the quality of the thesis. Then a positive and very significant relationship was also found between the level of student mastery of the statistics course material and thesis quality. Finally, the hypothesis testing concluded that between the variables of student mastery of research methodology material and statistics course material, there was a positive and very significant relationship with the thesis quality of university students.